Pendampingan Pengenalan dan Pembuatan Alat-Alat Peraga IPA Pada Program Studi Pendidikan IPA - Samputri, Salma; Ramlawati, Ramlawati; Arif, Rifda Nur Hikmahwati; Muhiddin, Nurhayani H; Muhiddin, St. Mulia Alfiyanti (UNIB Press, 2024)
Science teaching aids (props, experimental equipment) are tools used to teach students something so that they can learn something in their subject. Based on the community service results obtained, it can be concluded that the response from alumni of the Science Education Study Program, Faculty of Mathematics, Makassar State University regarding 1) Understanding teaching aids, namely 88.2%, strongly agreed, and the other 11.8% answered agree. 2) 76.5% of the tools used to make the props strongly agreed and the other 23.5% answered agree. 3) Responses regarding various types of props were 76.5% strongly agree, and the other 23.5% answered agree.